Views of Final Phase Undergraduate Medical Students’ of Bangladesh about the Socio-Economic and Institutional Factors that Influence Their Future Career - Ullah, Hadi Md Habib; Mostafa, Asma; Talukder, Mohammad Abu Sayeed; Sohel, Md Ibrahim (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Medical education is one of the most stressful field of education because of its highly demanding professional and academic requirements. There is a significant amount of factors as predictors of medical career decision-making: perceptions of specialty characteristics gained from curricular, extracurricular and personal experiences in health care, personal career needs (e.g Expected income, career options, status, work-life balance, labor content, lifestyle and working hours) and gender. An understanding of the factors which influence doctors’ career choices and how attitudes vary among doctors who choose different specialties, is important for all those involved in the teaching and training of doctors. This study was done to explore views of final phase undergraduate medical students of Bangladesh about the Socio-Economic & Institutional Factors that influence their future career selection. Materials and methods: This descriptive cross sectional study was conducted among 784 students randomly selected from eight medical colleges of Bangladesh, in the period of January 2019 to December 2019 with a pre tested self-administered questionnaire. Results: Study revealed that a total of 784 students responded, out of which 318(40.6%) males and 466(59.4%) female. Among them 726(92.6%) students wanted to do postgraduation. The leading reasons for selecting future career were future workload 255(38.2%), future workplace 272(39.8%) social status 242(35.6%) and scope of job 244(36.1%). Career choice also influenced by teachers as a role model 244(34.3%) Conclusion: Study recommended that career counseling during and after completion of graduation in the medical college, this stimulate students to gain experiences in different specialties. Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 62-65